m6A Methyltransferase METTL3 Promotes the Progression of Primary Acral Melanoma via Mediating TXNDC5 Methylation - Yue, Zhanghui; Cao, Meng; Hong, Anlan; Zhang, Qian; Zhang, Guoqiang; Jin, Zhibin; Zhao, Liang; Wang, Qiang; Fang, Fang; Wang, Yan; Sun, Jianfang (Frontiers in Oncology, 2022)
m6A modification is one of the most important post-transcriptional modifications in RNA and plays an important role in promoting translation or decay of RNAs. The role of m6A modifications has been highlighted by increasing evidence in various cancers, which, however, is rarely explored in acral melanoma. Here, we demonstrated that m6A level was highly elevated in acral melanoma tissues, along with the expression of METTL3, one of the most important m6A methyltransferase. Besides, higher expression of METTL3 messenger RNA (mRNA) correlated with a higher stage in primary acral melanoma patients. Knockdown of METTL3 decreased global m6A level in melanoma cells. Furthermore, METTL3 knockdown suppressed the proliferation, migration, and invasion of melanoma cells. In METTL3 knockdown xenograft mouse models, we observed decreased volumes and weights of melanoma tissues. Mechanistically, we found that METTL3 regulates certain m6A-methylated transcripts, thioredoxin domain containing protein 5 (TXNDC5), with the confirmation of RNA-seq, MeRIP-seq, and Western blot. These data suggest that METTL3 may play a key role in the progression of acral melanoma, and targeting the m6A dependent-METTL3 signaling pathway may serve as a promising therapeutic strategy for management of patients of acral melanomas.